ANALISIS KEBUTUHAN PENGEMBANGAN MEDIA PEMBELAJARAN DARING PADA MATA KULIAH LITTÉRATURE FRANÇAISE BERBASIS CANVA - Elvi Syahrin; Wahyuni Sa'adah; Balduin Pakpahan (BAHAS, 2021)
Abstract Learning the Littérature Française course online is relatively monotonous and less interesting. This is indicated by the stunted  attention and participation of students in attending lectures. This has an impact on the poor learning achievement for the subject which in turn is one of the causes of the low language skills of students. To overcome these problems, it is necessary to develop an interesting and a creative online learning media based on Canva application in order to increase   student’s learning outcomes in the Littérature Française course. This article discusses the result of need analysis of developing the Canva-based online learning media in Littérature Française course which is the basis for the importance of this development research.Keywords: developing, media, online, canva, need analysis